HISTORICAL INFLUENCE IN TAFSIR AL-MISHBAH: A HERMENEUTICAL EXPLORATION THROUGH GADAMER'S LENS - Fitra, Akhmad Aidil; Harfi, Muhammad; Khusnadin, Muhammad Hafidz; Iffah, Izzatul; Siswanto (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2024)
An interpretation is inevitably influenced by the interpreter's historical context. This is also true for Quraish Shihab in his Tafsir Al-Misbah. This study aims to examine how history influenced Quraish Shihab's interpretation of Qs. Luqman (31): 6. Employing a qualitative text-based methodology and Hans-Georg Gadamer's hermeneutical analysis, the study reveals that Quraish Shihab's interpretation is shaped by two key factors. First, he was influenced by his father and teachers. Second, his academic background significantly impacted his thought process. These two factors collectively contributed to the construction of Quraish Shihab's moderate approach in interpreting the Qur'an in general, and Qs. Luqman (31): 6 in particular.